Modal decomposition of magnetic maps: the case of Cape Roberts aeromagnetic survey, Antarctica - Gambetta, Marco (Annals of Geophysics, 2009)
This paper proposes a digital enhancement tool for magnetic anomaly maps. The magnetic anomaly map is decomposedby means of Eigenvalue Decomposition into a number of orthogonal bases. The dataset is then filteredaccordingly to a specific variance pattern. The dataset is decomposed and the eigenvalues population is inspectedso that the variance is evaluated yielding the definition of two thresholds. Subsequently, the dataset isreconstructed into three subsets which hold different features respectively. The proposed filtering procedure isfirst tested with a synthetic signal and then applied to the data of Cape Roberts (Antarctica) aeromagnetic survey,flown over an off-shore rift basin. The proposed method appears to be efficient in noise removal and acts asa digital enhancement tool which provides TMI anomaly maps revealing hidden lineaments, otherwise not visible.The methodology effectiveness as a hidden lineaments detection tool has been checked against independentdata.